A renewed understanding of anti‐human globulin reagents: interference constraints using an optimization method in pretransfusion compatibility tests. Issue 3 (5th February 2021) - Wang, Si‐Si; Zhang, Huayu; Qu, Limei; Zhao, Zhen; Li, Lingbo
Abstract: Anti‐human globulin (AHG) reagents are widely applied in pretransfusion compatibility tests. The accuracy of detection with AHG reagents is mainly affected by irregular antibodies or cold agglutinins in blood samples, which are related to the human complement system. Although much has been written about various types and applications of AHG reagents, their characteristics, interference factors and optimal selection in pretransfusion compatibility tests still need to be further clarified. Here, we review clinical practice and basic studies that describe each AHG reagent, summarize the advantages and disadvantages of using different AHG reagents in the presence of cold agglutinins or complement‐fixing antibodies, explore the potential mechanisms by which the complement system influences detection with AHG reagents and address the question of how to optimally select AHG reagents for clinically significant antibody detection. Abstract : Flowchart for how to suppress interference through an optimized selection of AHG reagents in pretransfusion compatibility tests. This review summarizes the type and characteristics of AHG reagents, discusses the influence of the complement system and clinically insignificant antibodies and their potential mechanisms in the detection of irregular antibodies by AHG reagents, and explores optimized selection of AHG reagents according to the aims of the compatibility test. Arrows represent promotion effects, and the blunt ends are suppression effects.